Exploring Indirect Aspects in Motivation and Academic Achievement During The Pandemic - Ade Nurhopipah; Ida Nuraida; Jali Suhaman (JETL (Journal of Education, Teaching and Learning), 2021)
Online learning methodologies are the most influential factor in educational success. However, it cannot be denied that there are non-technical aspects that indirectly affect students' motivation and academic achievement after the Covid-19 pandemic occurred. This study involves paired t-tests, regression tests, and partial t-tests to analyze the factors that can indirectly shape student motivation and academic achievement in Indonesia's higher schools. The factors studied were related to economic condition, health, habits, and social interaction. The result shows significant changes in learning motivation, economic and health conditions, student interactions with friends and lecturers, student involvement in student activity units and religious activities, use of social media, and time spent reading. The Grade Point Accumulative (GPA) before the pandemic was influenced by learning motivation. However, during the pandemic, the GPA was not significantly affected by learning motivation. Before the pandemic, family engagement and student involvement in religious activities significantly influence the GPA. Meanwhile, the factors that influence learning motivation during the pandemic are student involvement in social activities, interaction with lecturers, health conditions, and time spent reading.